Interaction and Reflective Practice of the Teacher in the Classroom [Interação E Prática Reflexiva Do Docente Na Sala de Aula] [Interacción y Práctica Reflexiva del Docente en la Sala de Clase] - Villalta-Paucar, M (Research Center of Universidad Pedagogica Nacional, 2022)
This article analyzes the relationship between reflective practice and teacher-student interaction in first-grade classrooms of urban and rural schools in Chile. With a methodology of multiple cases, discourses and practices of 8 teachers were analyzed, with different times of participation (High / Low) in a Program of Accompaniment of the Pedagogical Practice in the classroom (pap) that promotes dialogues based on the criteria of the theory of Mediated Learning Experience. Classes were filmed and teachers were interviewed before and at the end of the pap. The results showed that the teachers with high participation in the pap have interaction in the classroom with more use of mediated dialogue structures and a more elaborate reflection on their practice. At the same time, differences are observed in the use of these dialogical structures, according to the time of teaching experience, the perception that the teachers have of the children, and the urban and rural contexts of the school. © 2022 Research Center of Universidad Pedagogica Nacional. All rights reserved.